A Boy with Reset Osmostat Who Developed Chronic Hyponatremia due to Hypothalamic Injury Caused By a Giant Arachnoid Cyst - Junko Naganuma; Satomi Koyama; Yoshiyuki Watabe; Shigemi Yoshihara (JCRPE)
Reset osmostat (RO) is classified as type C among the four subtypes of the syndrome of inappropriate secretion of antidiuretic hormone based on antidiuretic hormone (ADH) secretion. It is characterized by a lower plasma osmolality threshold for ADH excretion when plasma sodium concentration is reduced. We report the case of a boy with RO and a giant arachnoid cyst (AC). The patient had been suspected of having AC since the fetal period, and a giant AC in the prepontine cistern was confirmed by brain magnetic resonance imaging seven days after birth. During the neonatal period, there were no abnormalities in the general condition or blood tests, and he was discharged from neonatal intensive care at 27 days after birth. He was born with a -2 standard deviation score birth length and mild mental retardation. When he was six years old, he was diagnosed with infectious impetigo and had hyponatremia of 121 mmol/L. Investigations revealed normal adrenal and thyroid functions, plasma hypo-osmolality, high urinary sodium, and high urinary osmolality. The 5% hypertonic saline and water load tests confirmed that ADH was secreted under low sodium and osmolality conditions, and the ability to concentrate urine and excrete a standard water load; therefore, RO was diagnosed. In addition, an anterior pituitary hormone secretion stimulation test was performed, which confirmed growth hormone secretion deficiency and gonadotropin hyperreactivity. Hyponatremia was untreated, but fluid restriction and salt loading were started at 12 years old because of the risk of growth obstacles. The diagnosis of RO is important from the viewpoint of clinical hyponatremia treatment options.